6. A GIANT MUCOCELE OF THE ETHMOIDAL SINUS WITH ORBITAL COMPLICATIONS ON THE SAME SIDE: A CASE REPORT (Vietnam Journal of Community Medicine, 2025)
A giant ethmoidal mucocele causing orbital compression with vision loss is extremely rare. This article reports a case of a 62-year-old female with a giant mucocele in the ethmoidal sinus, presenting with progressive bulging and blurred vision in the left eye for three months. The patient underwent endonasal endoscopic surgery, resulting in successful recovery of vision and normal eye movement without proptosis.
Keywords: Mucocele; orbit; ethmoid sinus; bulging eye; blurred vision; endoscopic sinus surgery.